Attempts on Fluorinative Transformation of Selected Functionalized Cycloalkene Scaffolds through Aziridination/Aziridine-Opening Protocol - Novák, Tamás T.; Gömöry, Ágnes; Nonn, Melinda; Han, Jianlin; Kiss, Loránd (Synlett, 2024)
Studies on the transformations of some functionalized cycloalkene derivatives through their ring olefin-bond aziridination/aziridine opening with fluoride are presented. The selected model compounds submitted to fluorinative functionalization were an amino ester and diesters with a cyclohexene skeleton as well as a cyclopentene-fused β-lactam. Functionalization proceeded across a substrate-directed diastereoselective olefin-bond aziridination, followed by fluoride-mediated aziridine opening or intramolecular lactonization giving some fluorinated amino ester or amino lactone derivatives.
Keywords: amino ester; aziridine; fluorination; lactam; lactone